Optimization of the clothing production line in peruvian smes through the implementation of lean manufacturing: a case study - Bravo De Rueda Alarcon, Santiago (2024)
The sector of small and medium enterprises (SMEs) of clothing in Peru faces significant challenges that affect its efficiency and competitiveness, such as high production cycle times, delays in transfers due to inefficient plant design, lack of standardization of defective processes and products. These problems negatively impact profitability, product quality and customer satisfaction, making it imperative to develop improvement strategies. This study implemented lean manufacturing tools to address these inefficiencies. Systematic Layout Planning (SLP) and Poka Yoke were applied to reorganize the layout of the packaging area and prevent errors in the production process. The 6S methodology was used to improve the organization and safety of the work environment, while time and movement studies optimized the activities at the workstations. These tools were systematically selected and applied, based on rigorous data analysis to identify and mitigate the root causes of inefficiencies. Highlights include a reduction in cycle time from 15.5 minutes to 12.1 minutes, representing a 22% decrease. The 6S audit improved significantly, from a score of 1.4 to 4.5, an increase of 221%. The distance travelled by the operators was reduced from 738 meters to 470 meters, reflecting a reduction of 36%. Finally, reprocessing rates decreased significantly; for machine 1, from 15.9% to 5.16%, and for machine 2, from 13.3% to 3.57%, indicating improvements of 68% and 73% respectively. These improvements not only increased production efficiency and quality, but also increased daily production capacity from 690 to 895 garments and raised operational efficiency from 68.5% to 88.8%. In conclusion, the study shows that the implementation of Lean Manufacturing tools can significantly transform the efficiency of clothing SMEs in Peru, providing a clear and replicable methodology that can be adopted in other regions and industrial sectors to improve productivity and competitiveness.